Travel and travelers in the Chad Basin : the margins of tourism - (:unkn) unknown (My University, 2012)
This thesis is about travelers and traveling in the basin of Chad. It helps understand people's motivations of traveling and their different movements throughout the region. Familial visits constitute their main motivation to travel. Besides it, there are other motivations. Anyway, through this ceaseless movement around family through its practice and representations, there is a tourism and leisure need for an emerging middle class. This need for leisure is also expressed through foreigners' practices which seem to be quite different from that of non resident tourists. Both, they explore and value touristic sites of the region by their presence. Whatever their motivations. This mobility has an impact on the environment: that of traveling and leisure. It is marked with risk, first, through the perception of a region which has undergone recurrent conflicts but also by the real life while traveling on a non existing road. This risk is differently appreciated by African and European travelers who either integrate it in their travel and the practices of the environment depends or accept it by fatality without thinking. Tourism in Africa is not only the number of people practicing it but also both, different attitudes of populations marked by a lack of concern, a mistrust or interest towards it. Unequal touristic development of African countries comes from it.
Keywords: African Research